B!RTH: a mixed-methods survey of audience members’ reflections of a global women’s health arts and science programme in England, Ireland, Scotland and Switzerland - Nynke van den Broek; Mary McCauley; Joanne Thomas; Cristianne Connor (BMJ Open)
Objective Public engagement and science communication are growing as an important forum in the design and dissemination of research. The B!RTH programme is a partnership that uses theatre in combination with scientific expert panel discussions to raise awareness about the global inequality in women’s health and access to healthcare. As part of this project, we assessed the views and experiences of audiences participating in B!RTH events.Design We conducted a multi-site mixed-methods survey using paper-based questionnaires.Settings Data were collected at four B!RTH theatre and science events: Dublin (Ireland), Edinburgh (Scotland), Geneva (Switzerland) and Liverpool (England) after the performance of four plays and three expert panel discussions.Participants All audience members.Methods Descriptive analysis was conducted for the responses to the closed-ended survey questions, and thematic analysis was used for written free text provided.Results The estimated response rate was 42%; 363 members of the audiences responded. Most respondents had been emotionally moved by the performances (92.8%) and felt challenged and provoked (80.7%). Many respondents (73.6%) agreed that their eyes had been opened by new ideas. Five themes emerged from the free-text analysis: (1) an expression of thanks and positive feedback on the content and performance of the plays, (2) the benefit of and innovative use of art and science, (3) personal feelings in response to the plays and panel discussions, (4) the need for action and (5) suggestions for use of the plays and panel discussions in schools and universities to ‘bring to life the human story behind the statistics’.Conclusions The B!RTH programme highlights how art and science can be used in partnership and is an effective tool to engage the public, to deliver key messages and to raise awareness about inequalities in global maternal and reproductive healthcare issues.